The patient as victim and vector ethics and infectious disease - Battin, M. Pabst (Oxford : Oxford University Press, 2009)
'The Patient as Victim and Vector' is jointly written by four authors at the University of Utah with expertise in bioethics health law, and both clinical practice and public health policy concerning infectious disease.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Communicable diseases -- Moral and ethical aspects; Epidemics -- Prevention -- Moral and ethical aspects; Bioethics